(E)-1-[4-(Hexyloxy)phenyl]-3-(4-hydroxyphenyl)prop-2-en-1-one - Ibrahim Abdul Razak; Hasnain Hussain; Siti Muhaini Haris Fadzillah; Zainab Ngaini; Hoong-Kun Fun (Acta Crystallographica Section E, 2011)
In the title compound, C21H24O3, intermolecular O—H...O and C—H...O interactions form bifurcated acceptor bonds, generating R21(6) ring motifs. These ring motifs link the molecules into extended chains along [010]. The crystal structure is further stabilized by C—H...π interactions.